Optima : optimisation of policies for transport integration in metropolitan areas - European Commission. Directorate-General VII Transport (Transport research, 1998)
Executive summary (s. 2-6).
Keywords: Euroopan unioni : liikennepolitiikka; joukkoliikenne : EU-maat; kaupungit : liikenne; liikennesuunnittelu; suurkaupungit : liikenne